(untitled) (Research, Society and Development, 2020)
Objective: to assess, from the nurses’ perspective, the presence and extent of the attributes of primary health care. Methodology: an evaluative study with a quantitative approach, carried out through the application of the Primary Care Assessment Tool professional version, with 66 nurses. Descriptive analysis (mean and standard deviation) and analytical (Pearson coefficient with significance p < 0.05) were performed. Results: The Family Health units obtained the essential, derived and general score higher than the Primary Care units, indicating a high orientation for primary health care. The accessibility and availability of services was assessed with low orientation in both types of services. A negative and significant correlation was identified between nurses’ working time in Primary Care units and the attribute Comprehensiveness – Provided Services. Conclusion: Nurses need to implement the structuring elements of primary health care in their daily work to qualify and consolidate the assistance provided.